Reconstruction of the Meaning of the Story of the Prophet Yunus (a.s.) in Q.S. As-Sāffāt: 142 - 144 Perspective of Tafsir Maqashidi - Sapriadi; Esa Satria Harfian; Mohammad Rafi Al-Hakim (Jurnal test, 2026)
This study analyzes the story of the Prophet Yunus A. S. in QS. Verses 142–144 of As-Saffat are often discussed from modern rational and scientific perspectives, particularly regarding the possibility of human survival in the belly of a large fish. This discussion shows the conflict between religious interpretations and modern biological logic, which is increasingly gaining strength in the digital world. This research aims to reconstruct the understanding of the story of the Prophet Yunus through the maqashidi interpretation, as an effort to address rational skepticism without ignoring the theological truth in the Qur’an. The method used is qualitative research using literature studies, which includes analysis of relevant verses, books of interpretation from the past and modern, and related scientific sources. The findings of the study show that the word al-ḥut does not refer to a specific species of fish, but rather to a category of large fish as a whole, so it is not limited by modern biological assumptions. In addition, the story of the Prophet Yunus is understood as a theological reality that a combination of literal and symbolic meanings can explain. Using the tafsir of Maqashidi di, this story affirms the divine purpose in terms of soul protection, spiritual strengthening, and civility in preaching, so that it remains relevant to face the challenges of modern-day rationality.